Gamma glutamyl transferase in Type II diabetes mellitus patients attending tertiary care academic hospital - Rakesh Sinha; Sudhanshu Shekhar; Ravi Kant; Nibha; Chaitanya Prakash (Asian Journal of Medical Sciences, 2023)
Background: Diabetes mellitus (DM) is a clinical syndrome characterized by hyperglycemia due to absolute or relative deficiency of insulin. It is a leading cause of mortality and morbidity in adults worldwide, posing serious medical, socioeconomic, and rehabilitation problems. Rapid diagnosis plays an important role in the management of DM. Gama glutamyl transferase (GGT) is an example of one of these biomarkers. Aims and Objectives: The aim of the study was to study the correlation of GGT in Type 2 DM patients. Materials and Methods: The present cross-sectional study was carried out in the Department of Biochemistry, B.J. government Medical College and Sassoon General Hospital Pune, Maharashtra. The study period was from December 2015 to June 2017. A total of 70 newly diagnosed Type 2 DM patient aged between 40 and 60 years with blood glucose level more than 126 mg/dL in fasting and more than 200 mg/dL post-prandial were included in the study. Results: The mean GGT in control group was 26.5 U/L and in diabetic group was 58.5 U/L. The GGT values were significantly raised in diabetic (case group) as compared to control group (P<0.0017). Conclusion: GGT can be considered as an important biomarker in monitoring and preventing complication associated with Type 2 DM.